Physical, mechanical, and water vapor barrier properties of starch/cellulose nanofiber/thymol bionanocomposite films - Othman, Siti Hajar; Wane, Bilguisse Mamadou; Nordin, Norhazirah; Noor Hasnan, Noor Zafira; A. Talib, Rosnita; Karyadi, Joko Nugroho Wahyu (MDPI AG, 2021)
The application of starch films, such as food packaging materials, has been restricted due to poor mechanical and barrier properties. However, the addition of a reinforcing agent, cellulose nanofibers (CNF) and also thymol, into the films, may improve the properties of films. This work investigates the effects of incorporating different concentrations of thymol (3, 5, 7, and 10 wt.%) on physical, mechanical, water vapor barrier, and antibacterial properties of corn starch films, containing 1.5 wt.% CNF produced using the solvent casting method. The addition of thymol does not significantly affect the color and opacity of the films. It is found that the tensile strength and Young’s modulus of the films decreases from 10.6 to 6.3 MPa and from 436.9 to 209.8 MPa, respectively, and the elongation at break increased from 110.6% to 123.5% with the incorporation of 10 wt.% thymol into the films. Furthermore, the addition of thymol at higher concentrations (7 and 10 wt.%) improved the water vapor barrier of the films by approximately 60.0%, from 4.98 × 10—9 to 2.01 × 10—9 g/d.m.Pa. Starch/CNF/thymol bionanocomposite films are also found to exhibit antibacterial activity against Escherichia coli. In conclusion, the produced starch/CNF/thymol bionanocomposite films have the potential to be used as antibacterial food packaging materials.